Activated regulatory T cell regulates neural stem cell proliferation in the subventricular zone of normal and ischemic mouse brain through interleukin 10 - Wang, Jixian; Xie, Luokun; Yang, Chenqi; Ren, Changhong; Zhou, kaijing; Wang, Brian; Zhang, Zhijun; Wang, Yongting; Jin, Kunlin; Yang, Guo-Yuan (Frontiers in Cellular Neuroscience, 2015)
Recent studies have demonstrated that the depletion of Regulatory T cells (Tregs) inhibits neural progenitor cell migration after brain ischemia. However, whether Tregs affect neural stem/progenitor cell proliferation is unclear. We explored the effect of Tregs on neurogenesis in the subventricular zone (SVZ) after ischemia. Tregs were isolated and activated in vitro. Adult male C57BL/6 mice underwent 60 min transient middle cerebral artery occlusion (tMCAO). Then Tregs (1 × 105) were injected into the left lateral ventricle (LV) of normal and ischemic mouse brain. Neurogenesis was determined by immunostaining. The mechanism was examined by inhibiting interleukin 10 (IL-10) and transforming growth factor (TGF-β) signaling. We found that the number of BrdU+ cells in the SVZ was significantly increased in the activated Tregs-treated mice. Double immunostaining showed that these BrdU+ cells expressed Mash1. Blocking IL-10 reduced the number of Mash1+/BrdU+ cells, but increased the amount of GFAP+/BrdU+ cells. Here, we conclude that activated Tregs enhanced neural stem cell (NSC) proliferation in the SVZ of normal and ischemic mice; blockage of IL-10 abolished Tregs-mediated NSC proliferation in vivo and in vitro. Our results suggest that activated Tregs promoted NSC proliferation via IL-10, which provides a new therapeutic approach for ischemic stroke.